Development of a high density hemagglutinin protein microarray to determine the breadth of influenza antibody responses - Anthony L. Desbien; Neal Van Hoeven; Steven J. Reed; Allen C. Casey; John D. Laurance; Susan L. Baldwin; Malcolm S. Duthie; Steven G. Reed; Darrick Carter (BioTechniques, 2013)
We have developed an influenza hemagglutinin protein microarray to assess humoral recognition of diverse influenza strains induced by vaccination and infection. Each array consists of controls and 127 hemagglutinin antigens from 60 viruses, spotted in replicates to generate a single array of 1296 spots. Six arrays are configured on a single slide, which in the following analysis was probed simultaneously with 2 isotype-specific fluorescent secondary antibodies yielding over 15,000 data points per slide. Here we report the use of this system to evaluate mouse, ferret, and human sera. The array allows simultaneous examination of the magnitude of antibody responses, the isotype of such antibodies, and the breadth of influenza strain recognition. We are advancing this technology as a platform for rapid, simple, high-throughput assessment of homologous and heterologous antibody responses to influenza disease and vaccination.